2012
DOI: 10.1186/bcr3090
|View full text |Cite
|
Sign up to set email alerts
|

Balancing harms and benefits of service mammography screening programs: a cohort study

Abstract: IntroductionThe use of screening mammography is still under debate within the medical community. The aim of this study is to define a balance sheet of benefits (breast cancer mortality reduction) and harms (overdiagnosis) for mammography screening programs.MethodsWe compared breast cancer incidence and mortality in two cohorts of women, defined as 'attenders' or 'non-attenders' on the basis of the individual attitudes towards screening, who were invited to the first round of the Florentine screening program. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…A cohort study in Italy used the cumulative incidence method to investigate overdiagnosis in women aged 60–69 years at entry in the first round of the Florentine screening program. After 5–14 years follow-up, they found 5% overdiagnosis of invasive breast cancer alone and 10% overdiagnosis of invasive plus in situ breast cancer (1.10 (0.98–1.23); Puliti et al , 2012). Our estimate of overdiagnosis increases to 5% if follow-up is restricted to 7 years; however, this is less than the follow-up recommended (Independent UK Panel on Breast Cancer Screening, 2012), and the risk of overestimating overdiagnosis if follow-up is too short has been demonstrated (Duffy and Parmar, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in Italy used the cumulative incidence method to investigate overdiagnosis in women aged 60–69 years at entry in the first round of the Florentine screening program. After 5–14 years follow-up, they found 5% overdiagnosis of invasive breast cancer alone and 10% overdiagnosis of invasive plus in situ breast cancer (1.10 (0.98–1.23); Puliti et al , 2012). Our estimate of overdiagnosis increases to 5% if follow-up is restricted to 7 years; however, this is less than the follow-up recommended (Independent UK Panel on Breast Cancer Screening, 2012), and the risk of overestimating overdiagnosis if follow-up is too short has been demonstrated (Duffy and Parmar, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown large variation in the estimates of overdiagnosis, ranging from less than 1 to 54% . Estimates have been higher in studies based on aggregated data than in those based on individual data . This applied both for studies with and without DCIS included, and in studies related to invited or attending women.…”
Section: Discussionmentioning
confidence: 99%
“…In making these points, the critic may have missed the summary table of prior estimates of overdiagnosis we provided in our original supplemental online Appendix (repeated here in Table 3). The average overdiagnosis estimate in 12 studies from seven countries, including results from randomized controlled trials and retrospective general population studies, was 31.5%, 28% among studies in which the denominator was all cancer, and 24%, 33%, and 75% in 3 studies in which it was screen-detected cancers [18,[23][24][25][26][27][28][29][30][31][32][33]. Our best guess estimate of 31% is in the "middle of the pack.…”
Section: Using [Our] Methods There Is No Evidence Of Overdiagnosis Omentioning
confidence: 99%